Digitalization in Education - Effects on Classroom Management1 - Petrescu Ana-Maria Aurelia; Santi Elena Ancuța; Enache Roxana Constanța; Gorghiu Gabriel (Journal of Education, Society & Multiculturalism)
In the last decades, especially in the post-pandemic period, the digitization phenomenon has gained momentum in all sectors of social life, including the educational environment. In our opinion, the phenomenon of digitalization in education generates a multitude of effects at the level of classroom management, in relation to the following significant aspects: pedagogical/educational relations (between various educational actors: students, teachers, parents, educational managers, etc. ) the teaching style/educational style, the learning style of the student, the mode and degree of engagement/involvement of students and teachers in the decision-making process at classroom level, the strategies of communication and resolution of conflict situations arising in different educational contexts, the ways of managing time, stress and priorities, etc. Through this article we aim to carry out a multidimensional research, aimed at identifying the perceptions and the attitudes of the teachers and students in the investigated sample, regarding the effects of digitization on the management of the classroom, in relation to the aspects listed above. The micro-survey sample included 103 pre-university teachers, with different specializations, who teach at different levels of education and 72 secondary school students (middle and high school). We appreciate that the answers obtained from the investigation carried out will contribute to the identification of valuable methodological landmarks from a socio-psycho-pedagogical point of view, useful in the direction of modernizing the management of the classroom and its realization in conditions of increased efficiency.